Effectiveness of Instructional Program on Parents’ Knowledge Concerning Management of Picky Eating Behavior among Children under Five Years of Age - Wameedh Hamid Shaker, Khatam M. Al-Mosawi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess parents’ knowledge concerning management of picky eating behaviors. To determine the effectiveness of instructional program on parents’ knowledge through comparing the knowledge scores at the pre-test and post-test. Methodology: To achieve the aims of this study, this quasi-experimental design was conducted on children suffering from picky eating behavior assigned to study and control groups is used to study the effectiveness of instructional program on parents’ knowledge toward dietary patterns for children with picky eating behavior at Al-Zahra Teaching Hospital in Al-Najaf Al-Ashraf City, and the study has been carried out during the period 25th February 2021 to 15th January 2022. Questionnaires were developed to determine the effectiveness of the instructional program on parents’ knowledge toward dietary patterns for children with picky eating behavior. The final instruments consisted of (4) parts First: concept of picky eating behavior in children (Includes four questions) Second: causes of picky behavior and dangerous factors (Includes eight questions) Third: symptoms of picky behavior (It includes six questions) Fourth: importance of a child’s picky eating behavior diet (It consists of seven questions) Fifth: ways to deal with the child picky eating behavior in food (It contains seven questions) Sixth: therapeutic and guiding measures for picky eating children (It has thirteen questions) Result: There is an improvement in the parents’ level of knowledge following the application of instructional program on parents’ knowledge Management of Picky Eating Behaviors for children Conclusion: According to the findings, the implementation instructional program session will positively change children’s nutritional status and dietary patterns. The difference between the two groups is related to the effectiveness of the dietary instruction program that was given to the study group parents but not to the control group parents. Recommendation: Establishing an educational center for parents in the hospital with adequate materials, media, audio-visual aids, and booklets for educating all parents on how to deal with their children’s eating behavior, pediatric nurses have more options for making information clear and easily understandable when communicating with parents and caregivers